Balance Training With a Vibrotactile Biofeedback System Affects the Dynamical Structure of the Center of Pressure Trajectories in Chronic Stroke Patients - Kodama, Kentaro; Yasuda, Kazuhiro; Kuznetsov, Nikita A.; Hayashi, Yuki; Iwata, Hiroyasu (Frontiers in Human Neuroscience, 2019)
Haptic-based vibrotactile biofeedback (BF) is a promising technique to improve rehabilitation of balance in stroke patients. However, the extent to which BF training changes temporal structure of the center of pressure (CoP) trajectories remains unknown. This study aimed to investigate the effect of vibrotactile BF training on the temporal structure of CoP during quiet stance in chronic stroke patients using detrended fluctuation analysis (DFA). Nine chronic stroke patients (age; 81.56±44 months post-stroke) received a balance training regimen using a vibrotactile BF system twice a week over four weeks. A Wii Balance board was used to record five 30 s trials of quiet stance pre- and post-training at 50 Hz. DFA revealed presence of two linear scaling regions in CoP indicating presence of fast- and slow-scale fluctuations. Averaged across all trials, fast-scale fluctuations showed persistent dynamics ( = 1.05 ± .08 for ML and  = 0.99 ± .17 for AP) and slow-scale fluctuations were anti-persistent ( = 0.35 ± .05 for ML and  = 0.32 ± .05 for AP). The slow-scale dynamics of ML CoP in stroke patients decreased from pre-training to post-BF training ( = 0.40 ± .13 vs. 0.31 ± .09). These results suggest that the vibrotactile BF training affects postural control strategy used by chronic stroke patients in the ML direction. Results of the DFA are further discussed in the context of balance training using vibrotactile BF and interpreted from the perspective of intermittent control of upright stance.